Diagnostic yield of proximal jejunal lesions with third‐generation capsule endoscopy. Issue 1 (12th June 2022) - Hirata, Issei; Tsuboi, Akiyoshi; Oka, Shiro; Sumioka, Akihiko; Iio, Sumio; Hiyama, Yuichi; Kotachi, Takahiro; Yuge, Ryo; Hayashi, Ryohei; Urabe, Yuji; Tanaka, Shinji
Abstract: Objectives: Capsule endoscopy (CE) has been shown to have poor diagnostic performance when the capsule passes quickly through the small bowel, especially the proximal jejunum. This study aimed to evaluate the diagnostic yield of proximal jejunal lesions with third‐generation CE technology. Methods: We retrospectively examined 138 consecutive patients, 76 (55.0%) of whom were men. The patients' median age was 70 years, and proximal jejunal lesions were detected by CE and/or double‐balloon endoscopy at Hiroshima University Hospital between January 2011 and June 2021. We analyzed the diagnostic accuracy of CE for proximal jejunal lesions and compared the characteristics of the discrepancy between the use of CE and double‐balloon endoscopy with Pillcam SB 2 (SB2) and Pillcam SB 3 (SB3). Results: SB2 and SB3 were used in 48 (35%) and 90 (65%) patients, respectively. There was no difference in baseline characteristics between these groups. Small‐bowel lesions in the proximal jejunum comprised 75 tumors (54%), 50 vascular lesions (36%), and 13 inflammatory lesions (9%). The diagnostic rate was significantly higher in the SB3 group than in the SB2 group for tumors (91% vs. 72%, p  < 0.05) and vascular lesions (97% vs. 69%, p  < 0.01). For vascular lesions, in particular, the diagnostic rate of angioectasia improved in the SB3 group (100%) compared with that in the SB2 group (69%). Conclusions: SB3 use improved the detection of proximal jejunal tumors and vascular lesions compared with SB2 use.